Odpowiedzi

Najlepsza Odpowiedź!
2010-03-08T21:04:09+01:00
[(a² - 9b²) : (a² + 2ab + b²)] : [(a+ 3b):(a+b)]=
[(a² - 9b²) : (a+b)²] : [(a+3b):(a+b)]=
[(a-3b)(a+3b) : (a+b)²] : [(a+3b):(a+b)]=
[(a-3b): (a+b)²] : [1:(a+b)]=
[(a-3b): (a+b)] : [1:1]=
[(a-3b): (a+b)] =
(a-3b):(a+b)
2010-03-08T21:07:06+01:00
[(a² - 9b²) : (a² + 2ab + b²)] : [(a+ 3b):(a+b)]=[(a² - 9b²) : (a+b)²] : [(a+3b):(a+b)]=[(a-3b)(a+3b) : (a+b)²] : [(a+3b):(a+b)]=[(a-3b): (a+b)²] : [1:(a+b)[(a-3b)(a+b)] : [1:1]=[(a-3b): (a+b)] =(a-3b):(a+b)